Child Neurology: A Case Series of Heterogeneous Neuropsychiatric Symptoms and Outcome in Very Early-Onset Narcolepsy Type 1. (7th June 2022) - Veneruso, Marco; Pizza, Fabio; Finotti, Elena; Amore, Giulia; Vandi, Stefano; Filardi, Marco; Antelmi, Elena; Nobili, Lino; Cassio, Alessandra; Pession, Andrea; Plazzi, Giuseppe
Abstract : Narcolepsy type 1 is a central disorder of hypersomnolence characterized by excessive daytime sleepiness, cataplexy (i.e., sudden loss of muscle tone during wakefulness triggered by emotions), and REM sleep-related manifestations that can present with a peculiar phenotype when arising at a pediatric age. Several features of childhood-onset narcolepsy type 1 are also common in neuropsychiatric conditions; discrete neuropsychiatric comorbidity has also been demonstrated. Here, we report on 3 children with very early narcolepsy type 1. All 3 patients had psychiatric features at the time of symptom onset coupled with peculiar motor disturbances. The course of narcolepsy symptoms also paralleled neuropsychiatric symptoms, suggesting a possible intrinsic link between sleep and psychological features. Multidisciplinary management is mandatory for pediatric narcolepsy type 1 since prompt disease management addressing neuropsychiatric symptoms could lead to better clinical outcomes and quality of life.